DESIGNING ORGANIZATIONAL AND METHODOLOGICAL SUPPORT FOR PEDAGOGICAL EDUCATION OF PARENTS IN THE CONDITIONS OF PRE-EDUCATIONAL INSTITUTIONS - (:unkn) unknown (Bright Mind Publishing, 2025)
The article reveals theoretical and methodological approaches to the design of organizational and methodological support for pedagogical education of parents in the context of a preschool educational organization (PEO). The key areas, forms and methods of education, as well as pedagogical conditions for effective interaction are presented. A model of organizational and methodological support with the identification of stages, content and expected results has been developed. Practical recommendations for the implementation of the system of interaction with parents are proposed. The material is addressed to preschool education specialists.
Keywords: Preschool education, pedagogical education, parents, interaction, methodological support, design, innovative forms.